Parental bonding, depression, and suicidal ideation in medical students - Tugnoli, Stefano; Casetta, Ilaria; Caracciolo, Stefano; Salviato, Jacopo (Frontiers in Psychology, 2022)
Background The psychological condition of university students has been the focus of research since several years. In this population prevalence rates of depression, suicidal ideation, anxiety disorders and substance abuse are higher than those of the general population, and medical students are more likely to have mental health issues than other students. Aims This study deals with the psychological condition of medical students, with a focus on correlations between depression, suicidal ideation and the quality of the perceived parenting style. Gender differences were also considered. Methods A cross-sectional study was conducted on a population of medical students, with an online questionnaire consisting of a personal data sheet for demographic and anamnestic data, and of three self-rating scales: the Beck Depression Inventory II (BDI-II), for the screening of depressive symptoms; the Beck Hopelessness Scale (BHS), to assess suicidal ideation; the Parental Bonding Instrument (PBI), to investigate the memory of the attitude of one's parents in the first 16 years of life. Two main affective dimensions were considered by PBI: “care” (affection and empathy) and “protection” (intrusiveness, controlling and constraint). Four different patterns of parenting styles are so evidenced: Neglectful Parenting (low care/low protection), Affectionless Control (low care/high protection), Optimal Parenting (high care/low protection), and Affectionate Constraint (high care/high protection). Results Overall, 671 students (182 males and 489 females) participated. Females, compared to males, experienced more distress and self-injurious behaviours, while males experienced more drugs or alcohol abuse. The BHS and BDI-II scores correlated positively with the PBI score for "protection" and negatively with that for "care". Affectionless Control and Neglectful Parenting were associated with higher medians of BHS and BDI-II scores. Conclusion The study confirms that the undergraduate medical student population has higher prevalence of depression and suicidal ideation than those detectable in the general population and that some specific parenting styles correlate with these two clinical variables. The impact of Affectionless Control and Neglectful Parenting on suicidal ideation and depressive symptomatology was more pronounced in females than in males. For males, the role of the father seemed to have less impact on the affective roots of suicidal thoughts and depression.